Max Weber Revisited, the Verstehen of Migration through Qualitative Research - Jorge A. BUSTAMANTE (El Colegio de la Frontera Norte, A.C., 2017)
This article begins with a reinterpretation of two basic concepts (Gemeinten Sinn and Verstehen ) in Webers theory of social relations. It defines international immigration as a social labor relation, characterized by an asymmetry of power between the principal ac - tors, namely, migrant workers and their employers. It refers to Ernesto Galarzas book entitled Merchants of Labor: The Mexican Bracero Story. It proposes the use of a partici - pant observation method in which the author poses as an undocumented/unauthorized Mexican immigrant, that is, as a subject in his own research. This research design cor - responds to a qualitative approach not aimed at an empirical test of hypotheses but instead focused on a deep understandingor what Max Weber understood by his methodological concept of Verstehen of social phenomena. A reference to an encoun - ter with a fellow inmate in a detention center led to an empirical foundation for the concept of vulnerability used in further explaining and measuring migrations.